Highly Interconnected Nanochannel and Silver, Nitrogen Co‐Doped Carbon Aerogel via Metal Organic Knot–Modifying as Active Polysulfide Immobilizer for Lithium–Sulfur Battery. Issue 1 (2nd December 2020) - Gao, Wei; Li, Xueliang; Ye, Jinjin; Zhu, Yunyun; Cheng, Sheng; Ding, Yunsheng
Abstract : The interconnected nanochannel and nitrogen, silver co‐doping carbon aerogels (CAs) are successfully prepared by in situ and sol–gel strategy. The as‐prepared materials with spherical structure show excellent sulfur loading of 72.6 wt% and specific surface area of 2064.5 m 2  g −1 . The active material as cathode for lithium sulfur battery can effectively suppress shuttle effect and display remarkable electrochemical performance due to the modification of tetra‐nuclear silver metal organic knots and polyethylene glycol for CA, the special modifiers provide more nanochannels for CA to significantly restrict the loss of sulfur. The prominent performance mainly benefits from the synergistic effect of interconnected nanochannel network structure and transition metal sulfide (Ag2 S) and nitrogen doping. Especially, the PEG‐Ag‐CA material delivers discharge capacity of 1313.6 mAh g −1 at a rate of 0.2C in first cycle, and retains 1143.8 mAh g −1 after 100 cycles. In addition, the theoretical calculations by density functional theory (DFT) further confirm the excellent absorption ability between prepared material and lithium polysulfide, and fully prove the absorption mechanism. Abstract : Interwoven nanochanneland nitrogen, silver‐doping carbon aerogels are successfully prepared by sol–gel strategy. The prominent performance mainly benefits from the synergistic effect of interconnected nanochannel network structure, transition metal sulfide, and nitrogen doping. Meanwhile, the theoretical calculations by density functional theory further confirm the excellent absorption ability between prepared material and polysulfide, and fully prove the absorption mechanism.